Evaluation of knowledge, awareness, and attitude toward emergency dental trauma management among the school teachers of Kolkata - Rahul Kaul; Parul Jain; Nilanjana Saha; Suchetana Goswami; Shantanu Mukhopadhyay; Subrata Saha; Subir Sarkar (Indian Journal of Dental Research, 2017)
Introduction: Traumatic dental injuries (TDIs) are very common in childhood. Majority of TDI occur at home followed by schools. The prognosis of TDIs to a great extent is dependent on prompt emergency measures taken at the site of accident. Hence, it is of paramount importance to assess the knowledge of people present at the site of accident that generally includes parents, teachers, and sports coaches. Aim of Study: The aim of the study was to assess the knowledge, attitude, and awareness of school teachers of Kolkata regarding management of TDIs. Materials and Methods: A cross-sectional survey was conducted on 400 school teachers of Kolkata over a period of 2 months using a pretested close-ended questionnaire. The questionnaire had three parts: Part 1 contained questions on personal information, Part 2 contained questions based on two imaginary cases of trauma, and Part 3 related to their attitude toward dental trauma education. Chi-square test was done to describe the strength of the associations. Results: : The overall knowledge of school teachers regarding management of TDIs was not found to be satisfactory. It was observed that most of the teachers were in favor of taking immediate professional consultation for the emergency management, but most of them were unaware of the steps to be taken on their part to minimize complications and improve prognosis. Conclusion: Despite the lack of knowledge and awareness regarding management of dental trauma, school teachers of Kolkata had a good attitude toward management of dental trauma and its education.